Pendampingan Kepesertaan BPJS bagi Masyarakat di Desa Paya Bujok Seuleumak Kecamatan Langsa Baro Kota Langsa - Afnina Afnina; Feri Gunawan; Siska Adela (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2022)
BPJS membership has been at 99.44% of the total population of Aceh, but BPJS officials are still trying to maximize JKN - KIS membership to 100%. The Community Service Team of STIKes Bustanul Ulum Langsa was called to carry out outreach activities and assistance in community insurance participation in Paya Bujok Seulemak Village, Langsa Baro District, Langsa City, attended by 23 participants consisting of community leaders, health cadres, Pokja management and RT administrators. This activity is carried out to provide awareness to the public about the importance of health insurance. The method of activities carried out is understanding through lectures and discussions on the reality of cases in the community regarding BPJS Insurance and providing assistance through direct practice in the field. Based on the results of the study, participants began to know what obligations must be fulfilled and their rights. Participants know the procedures or referral stages with various types of service items and types of drugs that are not covered by BPJS as well as sanctions and fines imposed by BPJS.